The Role of Proinflammatory Cytokine GM-CSF as A Therapy for Diabetic Ulcers: A Systematic Review - Pariyana Pariyana; Krisna Murti; Iche Andriyani Liberty; Muhammad Totong Kamaluddin (Indonesian Journal of Global Health Research, 2025)
Diabetic ulcers represent a prevalent complication among patients with poorly controlled diabetes mellitus, often resulting from inadequate blood glucose regulation, neuropathy, peripheral artery disease, and suboptimal wound care. This systematic review aims to evaluate the therapeutic efficacy of granulocyte-macrophage colony-stimulating factor (GM-CSF) for diabetic ulcers. The review utilized databases such as PubMed, ProQuest, and Google Scholar, with only six articles meeting the eligibility criteria for analysis. The findings suggest that GM-CSF exhibits therapeutic potential by enhancing neovascularization, promoting keratinocyte proliferation, facilitating granulation tissue formation, and reducing wound diameter. These results highlight the potential of GM-CSF as a therapeutic agent for diabetic ulcers. Nevertheless, the current body of research is limited, necessitating further studies with larger populations and diverse GM-CSF administration methods to substantiate these findings.